$\begin{aligned}[t]\lim\limits_{x\rightarrow1}\dfrac{\sqrt{x+3}-2}{x-1}&=\lim\limits_{x\rightarrow1}\dfrac{\left(\sqrt{x+3}-2\right)\left(\sqrt{x+3}+2\right)}{(x-1)\left(\sqrt{x+3}+2\right)}\\ &=\lim\limits_{x\rightarrow1}\dfrac{(x+3)-4}{(x-1)\left(\sqrt{x+3}+2\right)}\\ &=\lim\limits_{x\rightarrow1}\dfrac{x-1}{(x-1)\left(\sqrt{x+3}+2\right)}\\ &=\lim\limits_{x\rightarrow1}\dfrac{1}{\sqrt{x+3}+2}=\dfrac{1}{4}.\end{aligned}$ Do đó $\begin{aligned}[t]\lim\limits_{x\rightarrow1}\dfrac{\sqrt{x+3}-2x}{x-1}&=\lim\limits_{x\rightarrow1}\dfrac{\sqrt{x+3}-2-(2x-2)}{x-1}\\ &=\lim\limits_{x\rightarrow1}\dfrac{\sqrt{x+3}-2}{x-1}-\lim\limits_{x\rightarrow1}\dfrac{2x-2}{x-1}\\ &=\dfrac{1}{4}-\lim\limits_{x\rightarrow1}2=-\dfrac{3}{4}.\end{aligned}$